Employee participation in decision-making and organizational commitment: A study of modern organizations - Ogu, Sokari Jusih (Journal of Commerce, Management, and Tourism Studies, 2024)
This study explores the link between employee participation in decision-making and their commitment to the organization, with an emphasis on factors like job satisfaction, job security, and quality control. Using a mixed-method approach, data was gathered through quantitative surveys and qualitative interviews with employees from various sectors. The analysis aimed to assess how participation in decision-making affects organizational commitment. The findings show that employees who are involved in decision-making processes tend to have higher job satisfaction and a stronger sense of commitment to the organization. Participation fosters trust in leadership and a sense of ownership, leading to improved morale. However, some negative outcomes were noted, such as increased stress and conflict when decision-making processes are not transparent or well-managed. Job security was found to be a significant factor influencing employees’ willingness to engage in decision-making activities. The study concludes that fostering a culture of employee participation can enhance organizational commitment, but organizations must be mindful of potential challenges. Transparent, inclusive decision-making processes are essential for maximizing the benefits of participation while minimizing negative consequences. Future research should examine how different organizational structures impact employee participation and commitment.